Pengembangan Media Pembelajaran Digital Flipbook Berbasis Canva Pada Mata Pelajaran IPAS Materi Sistem Pernapasan Kelas V di Sekolah Dasar - Ita Mutiara Dewi; Novi Setyasto (Jurnal Penelitian Pendidikan IPA, 2024)
The lack of utilization of technology-based learning media at SDN 1 Sendangharjo affects the learning outcomes of students. This study is a research and development study that refers to the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This study aims to develop and test the feasibility, practicality, and effectiveness of a Canva-based Digital Flipbook. The population in this study consisted of 46 people with 12 subjects for a small-scale test on sixth-grade students and 24 subjects for a large-scale test on fifth-grade students at SDN 1 Sendangharjo. Data collection techniques used were tests (pretest-posttest) and non-tests in the form of observations, questionnaires, interview results, and document data. Validation results by media, material, and language expert validators showed that the Canva-based Digital Flipbook met valid criteria. Based on the pretest-posttest results, it was found that the Canva-based Digital Flipbook is effective in improving students' learning outcomes, as shown by the increase in the average pretest score from 50 to 80 at the posttest, with an N-Gain test result of 0.61 in the medium category. Based on the response questionnaire distributed, very positive responses were obtained from teachers and students. From these results, it can be concluded that the Canva-based Digital Flipbook is effective in improving students' learning outcomes and is feasible and practical to use in IPAS learning on the respiratory system material in the fifth grade at SDN 1 Sendangharjo